The Age of Insiders. The disappearance of the Outside - Grande, Helena (Re-visiones, 2024)
In this paper I present a reflection on the influence of the concept of globalization in the forms of organization and the disappearance of the outside as an idea of a possible independent system or space. In line with the exhibition The Whole Earth. California and the Disappearance of the Outside and the conference Documents, Constellations, Prospects, I propose, on the other hand, an analysis of the narratives arising within the Californian counterculture. On the other hand, I address certain theoretical approaches and artistic practices as examples of how we are rethinking the forms of organization, not as independent of an organized system but as an interstice within that same system.